Knowledge, Perception and Practices Regarding COVID-19 among frontline Nurses at Selected hospitals in Sri Lanka during COVID-19 Pandemic (International Journal of Occupational Safety and Health, 2024)
Introduction: The World Health Organization confirmed the COVID-19 epidemic situation as a public health emergency and is an emerging public health problem that has threatened millions of lives worldwide. Since COVID-19 has significantly affected the healthcare system globally, it is essential to update healthcare workers especially frontline nurses on the best practices for the proper management of the disease. The study aimed to assess Knowledge, Perceptions, and Practices regarding COVID-19 among frontline nurses at the National Institute of Infectious Diseases, National Hospital of Sri Lanka, and Base Hospital Mawanella in Sri Lanka.Methods: This cross-sectional study was conducted among 257 frontline nurses from main three hospitals in Sri Lanka from June 2020 to December 2021. A validated, pre-tested self-administered questionnaire was used for data collection. Kruskal Wallis test and Chi-square test were applied to find significant factors associated with good knowledge, using SPSS version 25.Results: The average age of the 257 participants was (31.8 ± 6.6) years and most (95%) of them were female. Of them, 79.4% had good knowledge, and the knowledge level of the nurses was significantly associated with their marital status (p=0.04) and their participation in the COVID-19 management workshop or lecture (p ≤0.001). There was a statistically significant median score difference between participants’ knowledge, and three hospitals (p